Indonesian Suburban Area EFL Teachers' Perspectives on Translanguaging - Maryansyah, Yupika; Syafryadin, Syafryadin; Badeni, Badeni; Heli yenti, Eva (UIN Salatiga, 2024)
Bilinguals and multilingual people use translanguaging, which is the technique of using different linguistic components or forms of independent languages to improve communication. When incorporated into teaching methods, translanguaging strategies enable educators to bridge linguistic gaps and support the learning of a foreign language. Despite the perceived advantages of translanguaging, variations in teachers' perceptions create ideological barriers, hindering students from fully embracing translanguaging. This study intends to investigate the perspectives of Indonesian teachers teaching in suburban areas on translanguaging in English language instruction in order to obtain a deeper knowledge of this subject. This study used semi-structured interviews using a qualitative research design to go deep into teachers’ insights on the topic. The result of the study shows that the participants had a generally positive perception on translanguaging and used a variety of translanguaging strategies in their teaching methods, such as the use of contextual cues, cooperation, student-centered approaches, and bidirectional translation. The result of this study also shows participants’ perspective on a crucial need to include translanguaging to support low proficiency level EFL students in their classrooms. In addition, the finding reveals teachers’ perspectives on ramifications of translanguaging when it is used in EFL classes. The findings can be valuable for education stakeholders, particularly in suburban areas, guiding design of lessons with translanguaging practices that cater to learners’ needs in English as a Foreign Language (EFL) classrooms.